Exploring Taiwanese Street Food in Contemporary Indonesian Society: Between Nostalgia and Gastrodiplomacy - Theresia Octastefani; Bayu Mitra A. Kusuma (Universitas Sultan Ageng Tirtayasa, 2022)
Food is an excellent means of creating an image and spreading influence. This study aims to explore Taiwanese street food as nostalgia and gastrodiplomacy in contemporary Indonesian society. This study uses a qualitative method with data collection through in-depth interviews and a literature study. The results showed that: first, food nostalgia tries to connect the past and the present. The feeling expressed by the Taiwanese diaspora on food will greatly depend on their previous lived experiences and homeland memories in the past, both personally and historically, with their present living circumstances in Indonesia. Second, gastrodiplomacy connects the relationship between the present and the future. The popularity of Taiwanese food in Indonesia is increasing, especially through boba and chicken Shilin consumption. This has a positive impact on building Taiwan's image. From food nostalgia and gastro diplomacy, we can learn about the past, present, and future relationships between people and nations.